Respiratory Diseases' Burden in children and adolescents of marginalized population: A retrospective study in slum area of Karachi, Pakistan - Sharif, Hina; Jan, Shah Sumaya; Sharif, Sana; Seemi, Tooba; Naeem, Hira; Rehman, Junaid (Frontiers in Epidemiology, 2023)
Background Worldwide, the burden of respiratory disease has dramatically increased, endangering public health. To our knowledge, there have been no reported cases of respiratory illness among children and adolescents living in the slums of Karachi, Pakistan. This study aimed to assess the burden of respiratory disease in marginalized slum populations and the factors causing such an increase in disease burden. Methods This study was conducted in 35 slums of Karachi, Pakistan, to determine the prevalence of respiratory disease in children and adolescents. Data on pneumonia, bronchitis, bronchiolitis, tuberculosis, and asthma from August 2019 to July 2022 were analyzed and inferences were drawn. Results Among the studied diseases, pneumonia was more prevalent among females (39,864, 44.9%), followed by males (19,006, 21.4%). Most of the children (59,988, 67.6%) were aged 1–5 years. In addition, of those diagnosed with pneumonia, 50,348 (56.8%) were from the same age group. Furthermore, bronchiolitis was found among 10,830 (12.2%) children aged 5–9 years. The majority (46,906, 52.9%) of the studied population belonged to the Pathan ethnicity, followed by Sindhi (21,522, 24.2%), and most of them (84,330, 95.1%) were of a lower socioeconomic status. Conclusions This study found that pneumonia is the most common respiratory disease followed by bronchiolitis in children and adolescents in a marginalized slum population of Karachi, Pakistan. Both pneumonia and bronchiolitis have seasonal variations in their occurrence.